Insight from electron density and energy framework analysis on the structural features of Fx‐TCNQ (x = 0, 2, 4) family of molecules. Issue 1 (11th February 2019) - Shukla, Rahul; Ruzié, Christian; Schweicher, Guillaume; Kennedy, Alan R.; Geerts, Yves H.; Chopra, Deepak; Chattopadhyay, Basab
Abstract : Charge density and energy framework analysis provide quantitative insights into the relevance of intermolecular interactions and transport properties in the fluoro‐substituted TCNQ family of molecules. Abstract : In this study, the nature and characteristics of the intramolecular and intermolecular interactions in crystal structures of the fluoro‐substituted 7, 7, 8, 8‐tetracyanoquinodimethane (TCNQ) family of molecules, i.e. F x ‐TCNQ ( x = 0, 2, 4), are explored. The molecular geometry of the reported crystal structures is directly dependent on the degree of fluorination in the molecule, which consequently also results in the presence of an intramolecular N[triple‐bond]C…F—C π‐hole tetrel bond. Apart from this, the energy framework analysis performed along the respective transport planes provides new insights into the energetic distribution in this class of molecules.